Ethical questioning in arts and health-based research: propositions and reflections - Afolabi, Taiwo; Kozak, Luba; Smith, Calum (Frontiers in Sociology, 2023)
Ethical questioning is a framework for considering the ethical implications and practices in research and is used as a tool for thinking about the connections between art and health. It enables researchers and practitioners to gain a deeper understanding of the emotional dimensions in the field of art and health. In this paper, we propose that ethical questioning, grounded in the principles of ethics of care, can foster a more reflexive and holistic approach to understanding the concept of well-being. We also propose that adopting ethical questioning as a methodology, which requires intentional self-reflection and recognition of positionality, can expose and challenge conventional knowledge hierarchies, resulting in more ethical research outcomes and relationships between researchers and participants. Ultimately, our hypothesis proposes that ethical questioning holds the potential to offer an actionable practice that demonstrates ethics of care.